ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TEDAFTAR DI BEJ - Abubakar Arif (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2006)
The objective of this study is to examine the usefulness of the financial ratios at individual and construct levels in predicting earning growth for one year ahead. To predict the earning growth, there are 15 financial ratios categorized into four constructs. This study used data taken from financial statements for three years (1999 2001) from 76 companies listed on Jakarta Stock Exchange.To examine the usefulness of financial ratios in order to predict earning growth, this study uses multiple regression analysis and Analysis of Moment Structure (AMOS). The multiple regression analysis is used to test the usefulness of the financial ratios at individual level while the Analysis of Moment Structure (AMOS) is used to test at the construct level to predict earning growth. The colleting data techniques used are library research and documentation from the Jakarta Stock Exchange. After data collected, it will be calculated and tested with statistic test in order to get a result. The next step is to take hypothesis from the result earlier and make a conclusion as the last step.The result of this study shows that changes of financial ratios at construct level which is debt ratio is useful to predict earnings changes for one year ahead in 76 companies listed in Jakarta Stock Exchange, whereas financial ratios at individual level are found unuseful.